Determination of the Prevalence and Antimicrobial Resistance of Enterococcus faecalis and Enterococcus faecium Associated with Poultry in Four Districts in Zambia - Grace Mwikuma; Henson Kainga; Simegnew Adugna Kallu; Chie Nakajima; Yasuhiko Suzuki; Bernard Mudenda Hang'ombe (MDPI AG, 2023)
The presence of antimicrobial-resistant Enterococci in poultry is a growing public health concern worldwide due to its potential for transmission to humans. The aim of this study was to determine the prevalence and patterns of antimicrobial resistance and to detect drug-resistant genes in Enterococcus faecalis and E. faecium in poultry from four districts in Zambia. Identification of Enterococci was conducted using phenotypic methods. Antimicrobial resistance was determined using the disc diffusion method and antimicrobial resistance genes were detected using polymerase chain reaction and gene-specific primers. The overall prevalence of Enterococci was 31.1% (153/492, 95% CI: 27.1-35.4). Enterococcus faecalis had a significantly higher prevalence at 37.9% (58/153, 95% CI: 30.3-46.1) compared with E. faecium, which had a prevalence of 10.5% (16/153, 95% CI: 6.3-16.7). Most of the E. faecalis and E. faecium isolates were resistant to tetracycline (66/74, 89.2%) and ampicillin and erythromycin (51/74, 68.9%). The majority of isolates were susceptible to vancomycin (72/74, 97.3%). The results show that poultry are a potential source of multidrug-resistant E. faecalis and E. faecium strains, which can be transmitted to humans. Resistance genes in the Enterococcus species can also be transmitted to pathogenic bacteria if they colonize the same poultry, thus threatening the safety of poultry production, leading to significant public health concerns.